Light-activatable and hyperthermia-sensitive “all-in-one” theranostics: NIR-II fluorescence imaging and chemo-photothermal therapy of subcutaneous glioblastoma by temperature-sensitive liposome-containing AIEgens and paclitaxel - Lixin Du; Pan Wang; Haiyan Huang; Menglong Li; Shubham Roy; Yinghe Zhang; Bing Guo (Frontiers in Bioengineering and Biotechnology, 2023)
Nowadays, it is still quite difficult to combat glioblastoma, which is one of the most lethal cancers for human beings. Combinatory therapy, which could not only improve therapeutic efficacy and overcome multiple drug resistance but also decrease the threshold therapeutic drug dosage and minimize side effects, would be an appealing candidate for glioblastoma treatment. Herein, we report fluorescence imaging in the second near-infrared window (NIR-II)-guided combinatory photothermal therapy (PTT) and chemotherapy of glioblastoma with a newly formulated nanomedicine termed PATSL. It is composed of temperature-sensitive liposome (TSL) carriers, NIR-II emissive and photothermal aggregation-induced emission (AIE) dyes, and chemotherapeutic paclitaxel (PTX) as well. PATSL shows spherical morphology with diameters of approximately 55 and 85 nm by transmission electron microscopy and laser light scattering, respectively, a zeta potential of −14.83 mV, good stability in both size and photoactivity, strong light absorption with a peak of approximately 770 nm, and bright emission from 900 nm to 1,200 nm. After excitation with an 808-nm laser with good spatiotemporal controllability, PATSL emits bright NIR-II fluorescence signals for tumor diagnosis in vivo, exhibits high photothermal conversion efficiency (68.8%), and triggers drug release of PTX under hypothermia, which assists in efficient tumor ablation in vitro and in vivo. This research demonstrates that “all-in-one” theranostics with NIR-II fluorescence imaging-guided combinatory PTT and chemotherapy is an efficient treatment paradigm for improving the prognosis of brain cancers.